Dynamic laminar rerouting of inter-areal mnemonic signal by cognitive operations in primate temporal cortex - Masaki Takeda (Nature Portfolio, 2018)
Inter-areal interaction has been shown to support various cognitive functions. Here, the authors report that neurons in area 36 flexibly synchronize their activity with different layers of area TE within different epochs of a visually cued recall task suggesting dynamic rerouting of information.